PENERAPAN PERSYARATAN KECUKUPAN DAN KUALIFIKASI DOSEN PADA PROGRAM STUDI DI PERGURUAN TINGGI DI LUAR IBUKOTA PROVINSI (Studi di Kabupaten Toba Samosir dan Tapanuli Utara) - Fidelis Haposan Silalahi; Tan Kamello; Suhaidi Suhaidi; Mahmul Siregar (USU LAW JOURNAL, 2018)
ABSTRACT   Among the standars maintained by the regulation of the Minister of research technology and higher education number 44 year 2015 about the national standars of higher education, there is a standar to give guidance for the qualification and number of lecturers a study program should have in any university in Indonesia as it is written on chapter 27 verse 6, chapter 29 verse 3 and 4.  From the study, it was found that the standar remained the same throughout Indonesia for the number of lecturers which is at minimum 6 persons per program study. Meanwhile, the qualification for the lecturers teaching in Diploma 3 and Diploma 4 programs is any lecturer holding a Master degree or an applied Master degree whose specialty is in line to the study program. However, for the implementation of the regulation of the Minister of research technology and higher education number 44 year 2015 that says every study program must have at least 6 permanent lecturers was still not fulfilled in academicals universities and the lecturers’ qualification was still not met since they were mostly bachelor graduates. Finally, the regulation of the Minister of research technology and higher education number 44 year 2015 cannot be adopted fully in every region because there are some discrepancies in abilities between the universities in capital cities and in urban areas. It is suggested that the regulation of the Minister of research technology and higher education number 44 year 2015 is not totally applied in universities outside capital cities of provinces like the regencies of Toba Samosir and North Tapanuli. It is also necessary to set the time limit for the application of the regulations. It is highly recommended that academicals universities are given time and exception in applying the rules for the lecturers’ adequacy and qualification. Finally, the support from the central and local governments are highly expected to successfully run the programs set by the Minister of research technology and higher education number 44 year 2015.   Key words : lecturer, standar for adequacy and qualification , study program